Bioethics of the refusal of blood by Jehovah's Witnesses: Part 3. A proposal for a don't-ask-don't-tell policy. - Muramoto, O (1999)
Of growing concern over Jehovah's Witnesses' (JWs) refusal of blood is the intrusion of the religious organisation into its members' personal decision making about medical care. The organisation currently may apply severe religious sanctions to JWs who opt for certain forms of blood-based treatment. While the doctrine may be maintained as the unchangeable "law of God", the autonomy of individual JW patients could still be protected by the organisation modifying its current policy so that it strictly adheres to the right of privacy regarding personal medical information. The author proposes that the controlling religious organisation adopt a "don't-ask-don't-tell" policy, which assures JWs that they would neither be asked nor compelled to reveal personal medical information, either to one another or to the church organisation. This would relieve patients of the fear of breach of medical confidentiality and ensure a truly autonomous decision on blood-based treatments without fear of organisational control or sanction.